1997
DOI: 10.1111/j.1442-2042.1997.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative UFT Adjuvant and the Risk Factors for Recurrence in Renal Cell Carcinoma: A Long‐Term Follow‐Up Study

Abstract: Background: Radical nephrectomy is the standard therapy for low-stage renal cell carcinoma. However,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Sensitivity analyses included 2 additional studies that reported CSS instead of OS and provided similar results, with a modest R‐squared of 0.48 for the 5‐year DFS and OS/CSS correlation and an R‐squared of 0.54 for the treatments effects (Table ). Additional sensitivity analyses were performed to assess for a correlation with earlier endpoints of 3‐year and 4‐year DFS rates and 5‐year OS rates.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Sensitivity analyses included 2 additional studies that reported CSS instead of OS and provided similar results, with a modest R‐squared of 0.48 for the 5‐year DFS and OS/CSS correlation and an R‐squared of 0.54 for the treatments effects (Table ). Additional sensitivity analyses were performed to assess for a correlation with earlier endpoints of 3‐year and 4‐year DFS rates and 5‐year OS rates.…”
Section: Resultsmentioning
confidence: 91%
“… A total of 12 trials; the trials by Hinotsu et al and Naito et al were excluded because HRs could not be calculated due to incomplete information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Another trial testing chemotherapy with adjuvant UFT (tegafur and uracil) was also unsuccessful. 31 Therefore, no treatment has demonstrated substantial and consistent benefit in the adjuvant setting for renal cell carcinoma, whether using immunotherapy, radiotherapy, hormonal therapy, or chemotherapy. Trials testing targeted therapies will be reviewed in the next section, because none of them have published final results and are still ongoing, some of them still accruing patients, and some others closed and with results pending.…”
Section: Other Treatment Modalitiesmentioning
confidence: 99%
“…Im Vergleich zu einem historischen Kollektiv ergab sich zwar ein signifikanter Unterschied (p < 0,01) hinsichtlich des 1-Jahres-Überlebens, jedoch wird dies auch von den Autoren nur als Argument für die Durchführung einer prospektiv randomisierten Studie gewertet. Wie beim metastasierenden Nierenzellkarzinom muû auch im adjuvanten Einsatz die Chemotherapie als weitgehend unwirksam betrachtet werden ( [17,19]; Tabelle 1).…”
Section: Chemotherapieunclassified